THE INFLUENCE OF CURRENT RATIO AND NET PROFIT MARGIN TO DIVIDEN PAYOUT RATIOON THE LISTED COMPANIES IN LQ 45 INDONESIA STOCK EXCHANGE (February-July 2016) - Susi Herawati (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2018)
This research is conducted to know the influence of Current Ratio and Net Profit Margin variable to Dividend Payout Ratio at companies listed in Index LQ 45 Indonesia Stock Exchange period February-July 2016. The population in this research is 45 financial statements of companies listed in index LQ 45 Indonesia Stock Exchange period February-July 2016. Sampling technique used is purposive sampling with criteria: (1) Companies listed in index LQ 45 period February-July 2016 (2) Companies that consecutively pay dividends during the 2011-2014 research period. (3) Companies that have complete data of financial statements,especially data used in research such as Current Ratio, Net Profit Margin and Dividend Payout Ratio. Samples were obtained by 18 companies. Analytical technique used is multiple linear regression and hypothesis test using t test with 5% confidence level and classical assumption test which include normality test,multicolinierity test, heteroscedasticity test and autocorrelation test. The results showed that the Current Ratio and Net Profit Margin have a significantpositive effect on Dividend Payout Ratio.